(3cJGH aj GdCOYjI hGdRjGQIs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3aj UdGI GdLeGYI, dG jfHZj GdGTJZGd ` Hd dG NdGa eYdhe aj Cfg jLH Ydi GdeGehe eJGHYI GdEeGes
(3BNQgG (B:s
(3BNQgG(B: (3jG eLjQ jG eLjQ jG eLjQ Cf JQMefj aCfG Cgd, hEf JYPHfj aCfG Cgd hjG Cgd GdJbhi hjG Ggd GdeZaQI hjG CQMe GdQGMejf hNjQ GdfGUQjf hjG NjQ GdZGaQjf MSjH Gddg hfYe Gdhcjds
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs